2014
DOI: 10.1002/ijc.29065
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐200c inhibits autophagy and enhances radiosensitivity in breast cancer cells by targeting UBQLN1

Abstract: Radioresistance is a major challenge during the treatment of breast cancer. A further understanding of the mechanisms of radioresistance could provide strategies to address this challenge. In our study, we compared the expression of miR- Breast cancer is the most common cancer in women worldwide. 1 Radiotherapy is an important part of the treatment in most patients receiving breast-conserving surgery and displays significant clinical benefits, such as decreasing the risk of local recurrence and reducing the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 48 publications
3
74
3
Order By: Relevance
“…Recently, another target of miR-200c, ubiquilin 1, has been shown to positively regulate radio-resistance by enhancing IR-induced autophagy in MDA-MB-231 breast cancer cells. Ectopic expression of miR-200c reversed the phenotype and sensitized the cells to radiation [71]. Furthermore, nanoparticle-assisted delivery of miR-200c has been shown to inhibit CSC-like properties and to augment radiosensitivity in three different gastric cancer cell lines [72].…”
Section: Mir-200c and Radiotherapy Resistancementioning
confidence: 99%
“…Recently, another target of miR-200c, ubiquilin 1, has been shown to positively regulate radio-resistance by enhancing IR-induced autophagy in MDA-MB-231 breast cancer cells. Ectopic expression of miR-200c reversed the phenotype and sensitized the cells to radiation [71]. Furthermore, nanoparticle-assisted delivery of miR-200c has been shown to inhibit CSC-like properties and to augment radiosensitivity in three different gastric cancer cell lines [72].…”
Section: Mir-200c and Radiotherapy Resistancementioning
confidence: 99%
“…A large amount of recent studies have shown that tumor resistance to radiation therapy is often associated with the upregulation of autophagy in many kinds of tumor cell lines, such as colon cancer cells, prostate cancer cells, malignant glioma cells, nasopharyngeal carcinoma cells, and breast cancer cells (17,18). The putative cytoprotective function of autophagy induced by radiation is generally considered to reflect the capacity of the cell to eliminate toxic species such as free radicals and damaged and unwanted proteins or organelles to generate energy and metabolic precursors (19).…”
Section: The Role Of Autophagy In Radiotherapymentioning
confidence: 99%
“…Recently, autophagy has been publicized to play a critical role in tumorigenesis. MiRNAs were identified to modulate cancer chemo-and radio-sensitivity via autophagy [81,82]. It was reported that norcantharidin (NCTD) could suppress miR-129-5p to provoke autophagic cell death and cell proliferation arrest in prostate cancer cells, which may increase cell autophagy via Beclin-1 as an initial cellular response to the toxicity of NCTD [83].…”
Section: Mir-129 and Autophagymentioning
confidence: 99%